Denaturing Gradient Gel Electrophoresis and Barcoded Pyrosequencing Reveal Unprecedented Archaeal Diversity in Mangrove Sediment and Rhizosphere Samples - Pires, Ana C. C. (American Society for Microbiology, 2012)
Mangroves are complex ecosystems that regulate nutrient and sediment fluxes to the open sea. The importance of bacteria and fungi in regulating nutrient cycles has led to an interest in their diversity and composition in mangroves. However, very few studies have assessed Archaea in mangroves, and virtually nothing is known about whether mangrove rhizospheres affect archaeal diversity and composition. Here, we studied the diversity and composition of Archaea in mangrove bulk sediment and the rhizospheres of two mangrove trees, Rhizophora mangle and Laguncularia racemosa, using denaturing gradient gel electrophoresis (DGGE) and pyrosequencing of archaeal 16S rRNA genes with a nested-amplification approach. DGGE profiles revealed significant structural differences between bulk sediment and rhizosphere samples, suggesting that roots of both mangrove species influence the sediment archaeal community. Nearly all of the detected sequences obtained with pyrosequencing were identified as Archaea, but most were unclassified at the level of phylum or below. Archaeal richness was, furthermore, the highest in the L. racemosa rhizosphere, intermediate in bulk sediment, and the lowest in the R. mangle rhizosphere. This study shows that rhizosphere microhabitats of R. mangle and L. racemosa, common plants in subtropical mangroves located in Rio de Janeiro, Brazil, hosted distinct archaeal assemblages.